(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
This is a descriptive, associative study with the objective of verifying the relationship between coping and anxiety, between coping and depression state. A research was done on 78 women in hypertension treatment at INCor through three inventories – Folkman and Lazarus coping, Spilberger anxiety, Beck depression. The data was submitted to statistic analysis at significance level of 5%. The sample presented, on its majority, moderate trait mean and anxiety state, depression symptoms mean compatible with absence of symptoms and distancing was the coping which prevailed. The data showed strong association between depression and less effective coping (p 0,003) and there has not been significant statistic difference between coping and anxiety.